Orthodontic Journals in South Asia: The longer you look back, the greater you can leap ahead - Gyawali, Rajesh (Orthodontic Journal of Nepal, 2017)
Orthodontic Journal of Nepal, Vol. 7 No. 1, June 2017 p.5-6